An ultra‐small cavity‐backed sector antenna with fractal transmission lines and NRI‐TLs for VHF application. Issue 11 (11th October 2018) - Cao, Wei‐ping; Sun, Chengjie; Li, Jinxin; Li, Simin; Lin, Yiyu
Abstract: A novel ultra‐small cavity‐backed sector antenna with fractal transmission lines (FTLs) and negative refractive index transmission lines (NRI‐TLs) is proposed in this paper. The proposed antenna comprises three parts. The first one is a U‐shaped cavity‐backed antenna composed of a planar double‐sector patch and a U‐shaped backed‐cavity. The other two parts are FTLs and NRI‐TLs, respectively, both of which are used to achieve bandwidth enhancement and size reduction for the U‐shaped cavity‐backed antenna. Although the U‐shaped cavity‐backed antenna and the proposed antenna have the same size of 36 cm × 40 cm × 25 cm, the proposed antenna can operate in a lower frequency band. Due to the introduction of the negative refractive index transmission lines, the overall size reduction is up to 12.3%. With features such as ultra‐small size, moderate bandwidth and good radiation property, the proposed antenna can meet the demanding requirements to the application of UAV airborne system.